PTL : the rise and fall of Jim and Tammy Faye Bakker's evangelical empire - Wigger, John H., 1959- (New York, NY : Oxford University Press, 2017)
In 1974 Jim and Tammy Faye Bakker launched their television show, the PTL Club, from a former furniture store in Charlotte, N.C. with half a dozen friends. By 1987 they stood at the center of a ministry empire that included their own satellite network, a 2300-acre theme park visited by six million people a year, and millions of adoring fans. The Bakkers led a life of conspicuous consumption perfectly aligned with the prosperity gospel they preached. They bought vacation homes, traveled first-class with an entourage and proclaimed that God wanted everyone to be healthy and wealthy. When it all fell apart, after revelations of a sex scandal and massive financial mismanagement, all of America watched more than two years of federal investigation and trial as Jim was eventually convicted on 24 counts of fraud and conspiracy. He would go on to serve five years in federal prison. PTL is more than just the story of the rise and fall of the Bakkers, John Wigger traces their lives from humble beginnings to wealth, fame, and eventual disgrace. At its core, PTL is the story of a group of people committed to religious innovation, who pushed the boundaries of evangelical religion's engagement with American culture. Drawing on trial transcripts, videotapes, newspaper articles, and interviews with key insiders, dissidents, and lawyers, Wigger reveals the power of religion to redirect American culture. This is the story of a grand vision gone wrong, of the power of big religion in American life and its limits.
The DJ and the queen -- A show of his own -- Everyday in the USA -- Abundant life -- The emperor's new groove -- Look me in the eye -- Time bomb -- Special math -- Secret lives -- Four days and three nights -- Cover-up -- Saturday night -- Scandal -- Holy war -- Judgment day -- Epilogue: Apocalypse chow.
Includes bibliographical references (pages 339-391) and index.
Keywords: Bakker, Jim, -- 1940-; Messner, Tammy Faye, -- 1942-2007.; PTL Club (Television program); Television in religion -- United States; Fraud; Scandals; Evangelicalism -- United States -- History; Fundamentalism -- United States -- History; BIOGRAPHY & AUTOBIOGRAPHY -- Religious; HISTORY -- Social History; Religion -- Christian Ministry -- Evangelism; Bakker, Jim, -- 1940-; Messner, Tammy Faye, -- 1942-2007.; Scandals; Fraud; Evangelicalism; Fundamentalism; Television in religion; United States; History; Biographies